1997
DOI: 10.1007/s007050050103
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir therapy for cytomegalovirus-associated liver disease in immunocompetent or immunocompromised children

Abstract: Ganciclovir therapy was given intravenously to 20 children with cytomegalovirus (CMV)-associated liver disease, of whom 6 were immunocompetent and 14 were immunocompromised (9 had AIDS and 5 had solid tumors). Immunocompetent children had isolated liver disease diagnosed at birth (4 children), or systemic congenital CMV infection including liver disease (2 children). Ganciclovir was used following two regimens: A) 5 mg/kg twice daily for 8 to 86 days (mean 21); B) 7.5 mg/kg twice daily for 14 days followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…It has been reported that, rarely, acute CMV infection in patients with normal immune systems can cause massive hepatocellular necrosis and coagulopathy [28]. There are reports of effective ganciclovir treatment of acute CMV hepatitis in immunocompetent children [29,30]. Also, biochemical, serological, virological improvements have been reported in cases of neonatal cytomegalovirus cholestatic hepatitis treated with ganciclovir [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, rarely, acute CMV infection in patients with normal immune systems can cause massive hepatocellular necrosis and coagulopathy [28]. There are reports of effective ganciclovir treatment of acute CMV hepatitis in immunocompetent children [29,30]. Also, biochemical, serological, virological improvements have been reported in cases of neonatal cytomegalovirus cholestatic hepatitis treated with ganciclovir [31].…”
Section: Discussionmentioning
confidence: 99%
“…The first reports of the use of ganciclovir therapy for congenital CMV infection date to the late 1980s (75,206). In subsequent reports (16,60,76,117,124,175,185,186,220,272), ganciclovir has been shown to be generally safe and well tolerated when used in newborns and has appeared to be useful in the management of severe, focal end-organ disease (pneumonitis, hepatitis, etc.) in infants.…”
Section: Interventions Antiviral Drugsmentioning
confidence: 99%
“…An unusual aspect of the case is that the child had never presented previously with a disease suggestive of an immunodeficiency. In contrast with perinatal CMV infection, which can be a severe disease [2,3,4,5], CMV infection later in life is generally asymptomatic in immunocompetent children and adults. In rare cases, a self-limited mononucleosis-like syndrome with mild liver-test abnormalities can be present.…”
Section: Discussionmentioning
confidence: 99%
“…However, antiviral therapy can be beneficial in immunocompetent hosts, including adults, with severe acute or persistent CMV infection, as reported in a limited number of cases [3,5,6]. For example, nine immunocompetent infants and children aged 20 days to 33 months each received a 2-week-course of intravenous ganciclovir (n=6) in association with anti-CMV immunoglobulin (n=2) or anti-CMV immunoglobulin alone (n=1) for severe CMV disease [3,5].…”
Section: Discussionmentioning
confidence: 99%